Sleeve Gastrectomy Ameliorates Diabetes-Induced Cardiac Hypertrophy Correlates With the MAPK Signaling Pathway - Xu, Qian; Ding, Huanxin; Li, Songhan; Dong, Shuohui; Li, Linchuan; Shi, Bowen; Zhong, Mingwei; Zhang, Guangyong (Frontiers in Physiology, 2021)
Background: Cardiac hypertrophy as a main pathological manifestation of diabetic cardiomyopathy (DCM), is a significant complication of diabetes. Bariatric surgery has been proven to relieve DCM, however, whether it can alleviate diabetes-induced cardiac hypertrophy is undefined. Methods: Diabetic and obese rats were performed sleeve gastrectomy (SG) after having diabetes for 16 weeks. The rats were euthanized 8 weeks after SG. Metabolic parameters, heart function parameters, myocardial glucose uptake, morphometric and histological changes, and the expression level of mitogen-activated protein kinases (MAPKs) were determined and compared among the control group (CON group), diabetes mellitus group (DM group), sham operation group (SHAM group), and SG group. Results: Compared with the SHAM group, the blood glucose, body weight, insulin resistance, and other metabolic parameters were significantly improved in the SG group. There was also a marked improvement in myocardial morphometric and histological parameters after SG. Furthermore, the myocardial glucose uptake and heart function were reversed after SG. Additionally, SG significantly downregulated MAPKs, including p38 MAPKs, c-Jun N-terminal kinases (JNKs), and extracellular signal-regulated kinases 1/2 (ERK1/2). The expression of DUSP6, which dephosphorylates ERK1/2, was upregulated after SG. These findings suggest that SG ameliorated diabetes-induced cardiac hypertrophy via the MAPK signaling pathway. Conclusion: These results showed that SG ameliorated diabetes-induced cardiac hypertrophy by suppressing the MAPK signaling pathway and upregulating DUSP6. Therefore, this study provides a novel strategy for treating diabetes-induced cardiac hypertrophy.